LINEAR OBJECT'S POINT-CLOUDS OBTAINED FOR HORIZONTAL SHOOTING DIRECTIONS: QUANTIFYING ITS METRIC AND DENSITY QUALITY AS A FUNCTION OF OBJECT'S INCLINATION ANGLE - DJORDJEVIC Djordje; DJUKANOVIC Gordana; FILIPOVIC Dusan (Journal of Industrial Design and Engineering Graphics, 2015)
This paper investigates characteristics of metric and density quality of linear object's point-clouds (obtained for horizontal shooting directions) as a function of its inclination angle (measured from horizontal plane). Conclusion is that for a fixed focal length, horizontal shooting directions targeting center of object`s axes, 24 station-points uniformly radially distributed around it, Object's Photo-Coverage-Mean of 2.05%, and process-quality descriptors values that belong to recommended ranges, concerning metric quality, generated Clouds are more precise but less accurate and almost not prone to object’s inclination; density quality of these Clouds is characterized by precision and accuracy - slightly dependent on object's inclination: the lower the inclination angle, the higher the precision and accuracy; additionally, the lower the inclination, the lower the density.